An Investigation of Herding Prospects in the Pakistan Stock Exchange - Shaista Jabeen; Muhammad Farhan; Sayyid Salman Rizavi (International Journal of Business and Economic Affairs, 2023)
The present study investigates investors’ herding in Pakistan Stock Exchange (PSX) and its sectors. Assumptions have been made that fundamental information causes herd behaviour; as a result, prices automatically adjust to newly-arrived information and lead to efficient markets. However, it is also believed that fundamental information does not cause herd behaviour and leads to price instability. Intraday, daily, and weekly stock returns of 528 companies listed in the PSX have been used. Market-wide herd measure, i.e., Cross-Sectional Standard Deviation (CSSD), has been employed as a herding measure. Findings revealed that neither PSX nor its sectors demonstrate herd behaviour at any level. The study has some implications for investors regarding investment decision-making.